1984
DOI: 10.1111/j.1467-8624.1984.tb00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Ego Development and Psychopathology: A Study of Hospitalized Adolescents

Abstract: This paper explores the relationship between ego development and psychiatrically relevant behaviors in a group of hospitalized adolescents. Building on Loevinger's model of ego development, we administered the Sentence Completion Test to 114 adolescent girls and boys. To study psychiatric symptoms, Achenbach and Edelbrock's Child Behavior Checklist was used. With these procedures, the Achenbach and Edelbrock factor scores were compared to ego stage using correlational and multiple regression analyses. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…Ego development was found to be a robust compensatory Factor, having strong relationships in expected directions with three of the four indices of competence, that is, school grades, classroom assertiveness, and classroom disruptiveness. These results are consistent with several earlier empirical findings establishing that ego development is a significant concomitant of various aspects of adjustment and mental health (Browning & Quinlan, 1985;Frank & Quinlan, 1976;Hauser et al, 1984;Noam et al 1984).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ego development was found to be a robust compensatory Factor, having strong relationships in expected directions with three of the four indices of competence, that is, school grades, classroom assertiveness, and classroom disruptiveness. These results are consistent with several earlier empirical findings establishing that ego development is a significant concomitant of various aspects of adjustment and mental health (Browning & Quinlan, 1985;Frank & Quinlan, 1976;Hauser et al, 1984;Noam et al 1984).…”
Section: Discussionsupporting
confidence: 93%
“…Ego development, a construct conceptualized by Loevinger (1976), is a "master" trait refiecting character development which is related to various aspects of cognitive and interpersonal development, but which represents more than any of them considered individually (Hauser, 1976). Inclusion of ego development as a moderator variable in this study was based on previous research showing that levels of this construct are negatively reiated to various indices of coping Eind maladjustment (Browning & Quinlan, 1985;Frank & Quinlan, 1976;Hauser et al, 1984;Noam et al, 1984).…”
Section: Suniya S Luthar 601mentioning
confidence: 99%
“…Although Loevinger has argued against viewing ego development as a dimension, this has repeatedly been done in the empirical literature (e.g. Noam et al, 1984;Bond et al, 1983;Hauser et al, 1983). In the present study, ogive scores were used for the analyses.…”
Section: Resultsmentioning
confidence: 92%
“…Recent empirical studies of adolescents have shown that the amount of psychiatric symptoms as well as symptoms reflecting mechanisms of internalization and externalization are all negatively related to ego development (E.g. : Noam et al, 1984;Hauser d al., 1983). Style of defense has also been found to correlate with ego development, i.e.…”
mentioning
confidence: 99%
“…Blakeney and Blakeney (1976) found that among Massachusetts's most troubled adolescent girls, two thirds were caught in the moral confusion between moral stages two and three. Among his in patients at Mcl.ean's Hospital/Harvard Medical Center, Noam (Noam, Hauser, Santostefano, Garrison, Jacobsen, Powers, & Mead, 1984) found that the adolescents used a stage of moral development that was inadequate to solve the moral problems that adolescence presented to them.…”
Section: Moral Conflict and Stage Transitionmentioning
confidence: 99%